Analisis Faktor Risiko Penyelesaian Skripsi Mahasiswa Sistem Informasi Menggunakan Exploratory Factor Analysis (EFA) - Risah Subariah; Endin Fahrudin; Samso Supriyatna (Computer Journal, 2026)
Delayed study completion among undergraduate students is a complex issue associated with the interplay of internal and external factors. This study aims to identify and examine the dimensions of risk factors associated with delayed study completion among Information Systems students using Principal Component Analysis (PCA) with Varimax rotation. Primary data were collected through a structured questionnaire administered to 299 undergraduate students of the Information Systems Study Program, semesters 3 to 8, at UNPAM Viktor Campus, covering 17 operational indicators. The analysis reduced the 17 indicators into 4 major risk factor dimensions, explaining 50.15% of the total variance: (1) Mobilization & Work Factor (14.02%), (2) Lecturer Mentorship Factor (14.28%), (3) Academic Competence Factor (13.07%), and (4) Assistance & Integrity Factor (8.78%). Factor 4 (Assistance & Integrity) was characterized by indicators related to dependence on external resources, including the use of third-party/joki services (0.717), peer assistance (0.598), and AI tools (0.592). Factor loading evaluation also identified two weak indicators (trap items) with loadings below 0.40: P1 (Employment Status; 0.363) and P4 (Primary Transportation Mode; 0.194). These findings highlight the importance of hybrid thesis mentoring, assignment load management, and academic integrity oversight to support timely study completion.